RIDESHARING SYSTEM IMPLEMENTATION USING DIJKSTRA ALGORITHM IN STRUCTURING MERGED TRAVEL ROUTES - AMBIYA - NIM : 13513093 , KHALIL
Personal vehicles are very important in modern life. However, the means of motorized transportation is very much against the concept of preserving nature. Every year the number of vehicles in Indonesia is always increasing. To reduce CO2 emissions, the United Nation Environment Program calls on people to drive together, either by public transport, or by private transportation. Driving together on private vehicles can be done by carpooling or ridesharing. To facilitate the process of ridesharing, there are already some applications that help ridesharing, one of them is by listing the travel plans on news feeds or classify travel plans with partitioning set. Another related study is the driving path design algorithm along with the help of intermediate location. With these algorithms, we can look for relevant travel candidates, as well as improve the efficiency of shared travel. Therefore, this final project aims to implement the algorithm design of the joint travel path on the ridesharing system. In this final project, the process of finding the relevant travel plan by using temporal database and cosine similarity, calculating the distance between two points with euclidean geographic distance, querying data process on fire overpass, designing travel route with dijkstra algorithm, and calculation of travel efficiency together by comparing relevant travel. Tests are performed on features that are implemented on the system. Testing is done using several cases made and calculating the efficiency of the trips performed together. Based on functional testing, the system is able to facilitate the process of finding relevant travel. Furthermore, based on the performance test of the algorithm, the total distance traveled can be reduced by 50% depending on the travel plan of the rider and passenger.